Influence of plantation on microbial community in porous concrete treating polluted surface water. (February 2017) - Long, Yan; Bing, Yongxin; Zhang, Zhengke; Cui, Kai; Pan, Xiaokang; Yan, Xiongfeng; Li, Bingxin; Xie, Shuguang; Guo, Qingwei
Abstract: Porous concrete has found increasing applications in slope ecological protection and water purification. Indigenous microorganisms in porous concrete can play important roles in pollutant removal. However, the porous concrete microbial community and its associated influential factors remain essentially unclear. The current study investigated the influences of plantation and plant species on bacterial and archaeal communities in porous concrete unit treating polluted river water. Illumina MiSeq high-throughput sequencing revealed high microbial richness and diversity in both planted and unplanted porous concrete systems. Bacterial community had higher richness and diversity than archaeal community. The evident layer depth-related changes of microbial community richness, diversity and structure were observed in each porous concrete system. Microbial richness, diversity and structure in porous concrete unit were influenced by both plantation and plant species type. Moreover, Proteobacteria dominated in bacterial communities in both planted and unplanted porous concrete systems, while unplanted porous concrete system displayed much higher proteobacterial proportion than planted ones. Thaumarchaeota microorganisms accounted for a considerable proportion in archaeal communities in porous concrete units. Highlights: Microbial community in porous concrete is characterized. Plantation and plant species type influence microbial community. Bacteria have higher community richness and diversity than Archaea .